Cell-derived Newcastle disease virus variant with two amino acid substitutions near cleavage site of F shows favorable traits as oncolytic virus - Marco Huberts; J. Fréderique de Graaf; Daphne Groeneveld; Stefan van Nieuwkoop; Ron A.M. Fouchier; Bernadette G. van den Hoogen (Molecular Therapy: Oncology)
Newcastle disease virus (NDV) has shown encouraging effectiveness in in vitro, in vivo, and in early clinical trials as a viro-immunotherapy for pancreatic cancer. Previously, NDV used in clinical trials was produced in embryonated chicken eggs; however, egg-produced viruses are known to be partly neutralized by the human complement system when administered intravenously. Here, an NDV variant (NDV F0) was generated for production in mammalian cells, without passage in eggs. This was achieved by introducing the V-106-M and L-117-S amino acid substitutions upstream of the cleavage site in the F protein, resulting in rNDV F0-M, rNDV F0-S, and NDV F0-M/S. These viruses can be considered non-virulent as determined with in vivo pathogenicity testing and were neutralized less by the human complement system, which is explained by CD46 expression on the viral membrane. The inoculation of 10 pancreatic cancer cell lines demonstrated similar or enhanced replication and cell-killing efficacy of rNDV F0-M/S compared to rNDV F0 and rNDV F0-M. In conclusion, NDV F0 variants with M and S substitutions are non-virulent, effective oncolytic viruses that can be produced in mammalian cells, potentially resulting in a more effective treatment option for pancreatic cancer patients compared to rNDV F0.